14. PERAN HOME COUNTRY DALAM BISNIS PERUSAHAAN MULTINASIONAL: STRATEGI DIPLOMASI AMERIKA SERIKAT DALAM PERPANJANGAN KONTRAK CHEVRON DI INDONESIA TAHUN 2011-2013 - Risky Ananda Lubis; Ika Riswanti Putranti; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This research aims to describe United States foreign policy to extend the contract of Chevronin Siak Block, Riau, Indonesia. Chevron’s effort to extend its contract was not receivepositive feedback from Indonesia, because the profit sharing system or a Production SharingContract (PSC) that Indonesia have had changed. As the home country of Chevron, the usedof smart diplomacy in which both of soft and hard diplomacy employed in order to extend thecontract. This research uses both primary and secondary data. This research found that theextension of the Chevron’s contract in Siak Block, Riau, Indonesia was influenced by smartdiplomacy employed by the United State by combining elements of threat and persuasive suchas aid and lobbies.